2017
DOI: 10.1111/acel.12606
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin‐1 deficiency induces premature senescence with mitochondrial dysfunction

Abstract: SummaryParadoxical observations have been made regarding the role of caveolin‐1 (Cav‐1) during cellular senescence. For example, caveolin‐1 deficiency prevents reactive oxygen species‐induced cellular senescence despite mitochondrial dysfunction, which leads to senescence. To resolve this paradox, we re‐addressed the role of caveolin‐1 in cellular senescence in human diploid fibroblasts, A549, HCT116, and Cav‐1−/− mouse embryonic fibroblasts. Cav‐1 deficiency (knockout or knockdown) induced cellular senescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 45 publications
0
42
0
Order By: Relevance
“…In addition to the markers mentioned above, recent studies have uncovered new players and their role in the field of cellular senescence. Mitochondria can be affected by cellular senescence in several aspects such as caveolin-1 deficiency, which has been shown to induce cellular senescence by affecting the functionality of the mitochondria [ 93 ]. The other aspect is mitochondrial DNA hypomethylation, which is a feature of induced senenscence in human fetal heart mesenchymal stem cells and can be induced by reactive oxidative species [ 94 ].…”
Section: New Players In the Field Of Senescence?mentioning
confidence: 99%
“…In addition to the markers mentioned above, recent studies have uncovered new players and their role in the field of cellular senescence. Mitochondria can be affected by cellular senescence in several aspects such as caveolin-1 deficiency, which has been shown to induce cellular senescence by affecting the functionality of the mitochondria [ 93 ]. The other aspect is mitochondrial DNA hypomethylation, which is a feature of induced senenscence in human fetal heart mesenchymal stem cells and can be induced by reactive oxidative species [ 94 ].…”
Section: New Players In the Field Of Senescence?mentioning
confidence: 99%
“…Several previous studies using in vitro senescent cells [18] and in vivo aged tissues [17,37] have suggested that cav-1 expression is increased with aging. Additionally, cav-1 overexpression displays senescence phenotypes [20,38,39], suggesting that increased cav-1 expression may play an important role in aging at the cellular level, although there have been con icting observations that cav-1 knockout accelerates premature senescence in MEFs [40] and loss of cav-1 accelerates neurodegeneration and aging [41].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, caveolin-1 and integrins play critical roles in determining senescent cell morphology [48]. Recently, it was also reported that premature senescence induced by cavelin-1-deficiency is mediated by inhibition of mitochondrial respiration and oxidative phosphorylation complex I, a reduction in the NAD+/NADH ratio, and SIRT1 inactivation [49]. Activation of focal adhesion signaling induces PI3K-AKT signaling.…”
Section: Discussionmentioning
confidence: 99%